The Influence Of The Contextual Teaching And Learning Approach On Learning Out-comes In Multiples And Factors Of Integers Among 5th Grade Students At SDN Baru 06 - Muhammad Reza Fahlevi; Ishaq Nuriadin (Eduvest - Journal of Universal Studies, 2024)
This study aims to examine the impact of the Contextual Teaching and Learning (CTL) approach using concrete media, specifically the Snakes and Ladders game, on the learning outcomes of fifth-grade students in the topic of multiples and factors of whole numbers at SDN Baru 06. The research employed a quasi-experimental method involving two groups: an experimental group using the Snakes and Ladders game and a control group using traditional methods. Data were collected through pre-tests and post-tests and then analyzed using normality tests, linear regression, T-tests, and F-tests. The results showed that the CTL approach with the Snakes and Ladders game significantly improved students' learning outcomes compared to traditional methods. The average score of the experimental class was higher than that of the control class, with statistical analysis indicating a significant impact between the scores and the students' grades. This study suggests that the use of CTL with concrete media can make mathematics learning more engaging and effective, helping students better understand the material and relate knowledge to real life.